Kombinasi Rebusan Jahe dan Madu Menurunkan Tekanan Darah pada Lansia dengan Hipertensi - Hendri Heriyanto; Bayu Adhi Nugraha; Efrizon Hariadi (JURNAL KEPERAWATAN RAFLESIA, 2022)
Abstract Hypertension is a non-communicable disease. Hypertension is one of the world's health concerns, especially in developing countries because it is the highest cause of death in the world. Based on data from WHO, 26.4% or 972 million people on earth have hypertension. This study aims to determine the effect of ginger and honey decoction to reduce blood pressure in the elderly with hypertension. The research design is a quasi-experimental pre-post test with control group design. To find the sample used random technique. The number of respondents was 44 people in each intervention and control group totaling 22 people. The treatment was given a combination of ginger boiled water plus honey therapy, while the control group was given ginger boiled water with a frequency of giving once a day with a duration of 5 consecutive days. With the pre-measured initial blood pressure stage before being given treatment and post blood pressure was measured again after being given treatment. The data collection instrument used OneMed brand mercury tension meter and a questionnaire. Statistical test results using the Mann-Whitney systolic blood pressure p value 0.000 (p value ≤ α 0.05) diastolic blood pressure p value 0.000 (p value ≤ α 0.05). There is an effect of intervention by giving ginger and honey boiled water therapy to reduce blood pressure in elderly hypertensives.